Flashpoints in the war on terrorism - Reveron, Derek S.; Murer, Jeffrey Stevenson (Routledge, 2006)
Offers a comprehensive overview of international political violence by bringing together foreign policy experts on several regions who examine conflicts in the Fertile Crescent, the Balkans, the Post-Soviet Region, the Himalayas, Southeast Asia, and sub-Saharan Africa.